HLA-B*1502 in Iranian Children with Anticonvulsant Drugs-Induced Skin Reactions - TONEKABONI, Seyed Hasan; JAFARI, Narjes; MANSOURI, Mahboubeh; JABBEHDARI, Sayena; EFTEKHARI, Rahil; CHAVOSHZADEH, Zahra; ABDOLLAH GORJI, Fatemeh; MESDAGHI, mehrnaz (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Tonekaboni SH, Jafari N, Mansouri M, Jabbehdari S, Eftekhari R, Chavoshzadeh Z, Abdollah Gorji F, Mesdaghi M. HLA-B*1502 in Iranian Children with Anticonvulsant Drugs-Induced Skin Reactions. Iran J Child Neurol. Spring 2017; 11(2):26-30. Abstract Objective Anticonvulsant drugs can cause various forms of skin drug reactions, ranging from exanthema to severe blistering reactions. An association between HLA-B*1502 allele and severe skin reactions have been reported. Materials & Methods Fifteen patients with severe skin reactions following treatment with anticonvulsant drugs (Carbamazepine, lamotrigine, phenobarbital, primidone) and 15 controls (age-matched epileptic patients taking similar anticonvulsants without drug eruption) were included. They were referred to Mofid Children’s Hospital in Tehran, Iran, between Jan 2012 to Jan 2014. Genomic DNA was extracted from peripheral blood of all patients and HLA- B*1502 genotype was detected by real-time PCR. Results None of the patients was positive for HLA- B*1502, but two patients in control group had positive HLA- B*1502. Conclusion The HLA- B*1502 is not correlated with severe anticonvulsant drugs -induced skin reactions in Iranian children. References 1.Roujeau JC. Clinical heterogeneity of drug hypersensitivity. Toxicology 2005; 209: 123 –9. 2.McCormack M, Alfirevic A, Bourgeois S, Farrell JJ, Kasperavičiūtė D, Carrington M, et al. HLA-A*3101 and carbamazepine-induced hypersensitivity reactions in Europeans. N Engl J Med 2011; 364(12):1134-43. 3.Daly AK, Donaldson PT, Bhatnagar P, Shen Y, Pe’er I, Floratos A, et al. HLA-B*5701 genotype is a major determinant of drug-induced liver injury due to flucloxacillin. Nat Genetic 2009; 41:816–9. 4.Amstutz U, Ross CJ, Castro-Pastrana LI, Rieder MJ, Shear NH, Hayden MR, Carleton BC. CPNDS Consortium; HLA-A 31:01 and HLA-B 15:02 as genetic markers for carbamazepine hypersensitivity in children. Clin Pharmacol Ther 2013; 94(1):142-9. 5.Man CB, Kwan P, Baum L, Yu E, Lau KM, Cheng AS, Ng MH. Association between HLA-B*1502 allele and antiepileptic drug-induced cutaneous reactions in Han Chinese. Epilepsia 2007; 48(5):1015-8. 6.Zeng T, Long YS, Min FL, Liao WP, Shi YW. Association of HLA-B*1502 allele with lamotrigine-induced Stevens– Johnson syndrome and toxic epidermal necrolysis in Han Chinese subjects: a meta-analysis. Int J Dermatol 2015; 54(4):488-93. 7.Bastuji-Garin S, Rzany B, Stern RS, Shear NH, Naldi L, Roujeau JC. Clinical classification of cases of toxic epidermal necrolysis, Stevens-Johnson syndrome, and erythema multiforme. Arch Dermatol 1993; 129(1):92-6. 8. Hung SI, Chung WH, Jee SH, Chen WC, Chang YT, Lee WR, et al. Genetic susceptibility to carbamazepine-induced cutaneous adverse drug reactions. Pharmacogenet Genomics 2006; 16(4):297-306. 9. Wang Q, Zhou JQ, Zhou LM, Chen ZY, Fang ZY, Chen SD, et al. Association between HLA-B*1502 allele and carbamazepine-induced severe cutaneous adverse reactions in Han people of southern China mainlan. Seizure 2011; 20 (6):446-8. 10. Li LJ, Hu FY, Wu XT, An DM, Yan B, Zhou D. Predictive markers for carbamazepine and lamotrigine-induced maculopapular exanthema in Han Chinese. Epilepsy Res 2013; 106 (1-2):296-300. 11. Kim SH, Lee KW, Song WJ, Kim SH, Jee YK, Lee SM, et al; Adverse Drug Reaction Research Group in Korea. Carbamazepine-induced severe cutaneous adverse reactions and HLA genotypes in Koreans. Epilepsy Res 2011; 97 (1-2):190-7. 12. Criado PR, Criado RFJ, Avancini JM, Santi CG. Drug reaction with eosinophilia and systemic symptoms (DRESS)/drug-induced hypersensitivity syndrome (DIHS): a review of current concepts. An Bras Dermatol 2012; 87(3):435–49. 13. Chung WH, Hung SI, Hong HS, Hsih MS, Yang LC, Ho HC, et al. Medical genetics: a marker for Stevens– Johnson syndrome. Nature 2004; 428: 486. 14. Man CB, Kwan P, Baum L, Yu E, Lau KM, Cheng AS, Ng MH. Association between HLA-B*1502 allele and antiepileptic drug induced cutaneous reactions in Han Chinese. Epilepsia 2007; 48: 1015–8. 15. Locharernkul C, Loplumlert J, Limotai C, Korkij W, Desudchit T, Tongkobpetch S, et al. Carbamazepine and phenytoin induced Stevens–Johnson syndrome is associated with HLA-B*1502 allele in Thai population. Epilepsia 2008; 49:2087–91. 16. Kaniwa N, Saito Y, Aihara M, Matsunaga K, Tohkin M, Kurose K, et al. HLA-B locus in Japanese patients with anti-epileptics and allopurinol-related Stevens– Johnson syndrome and toxic epidermal necrolysis. Pharmacogenomics 2008; 9: 1617–22. 17. Alfirevic A, Jorgensen AL, Williamson PR, Chadwick DW, Park BK, Pirmohamed M. HLA-B locus in Caucasian patients with carbamazepine hypersensitivity. Pharmacogenomics 2006; 7: 813–8. 18. Tangamornsuksan W, Chaiyakunapruk N, Somkrua R, Lohitnavy M, Tassaneeyakul W. Relationship between the HLA-B*1502 allele and carbamazepine-induced Stevens- Johnson syndrome and toxic epidermal necrolysis: a systematic review and meta-analysis. JAMA Dermatol 2013; 149(9):1025-32.